Role of Intestinal Bacteria in Gliadin-Induced Changes in Intestinal Mucosa: Study in Germ-Free Rats - Cinova, Jana; De Palma, Giada; Stepankova, Renata; Kofronova, Olga; Kverka, Miloslav; Sanz, Yolanda; Tuckova, Ludmila (PLOS ONE, 2011)
Background and Aims Celiac disease (CD) is a chronic inflammatory disorder of the small intestine that is induced by dietary wheat gluten proteins (gliadins) in genetically predisposed individuals. The overgrowth of potentially pathogenic bacteria and infections has been suggested to contribute to CD pathogenesis. We aimed to study the effects of gliadin and various intestinal bacterial strains on mucosal barrier integrity, gliadin translocation, and cytokine production. Methodology/Principal Findings Changes in gut mucosa were assessed in the intestinal loops of inbred Wistar-AVN rats that were reared under germ-free conditions in the presence of various intestinal bacteria (enterobacteria and bifidobacteria isolated from CD patients and healthy children, respectively) and CD-triggering agents (gliadin and IFN-γ) by histology, scanning electron microscopy, immunofluorescence, and a rat cytokine antibody array. Adhesion of the bacterial strains to the IEC-6 rat cell line was evaluated in vitro. Gliadin fragments alone or together with the proinflammatory cytokine interferon (IFN)-γ significantly decreased the number of goblet cells in the small intestine; this effect was more pronounced in the presence of Escherichia coli CBL2 and Shigella CBD8. Shigella CBD8 and IFN-γ induced the highest mucin secretion and greatest impairment in tight junctions and, consequently, translocation of gliadin fragments into the lamina propria. Shigella CBD8 and E. coli CBL2 strongly adhered to IEC-6 epithelial cells. The number of goblet cells in small intestine increased by the simultaneous incubation of Bifidobacterium bifidum IATA-ES2 with gliadin, IFN-γ and enterobacteria. B. bifidum IATA-ES2 also enhanced the production of chemotactic factors and inhibitors of metalloproteinases, which can contribute to gut mucosal protection. Conclusions Our results suggest that the composition of the intestinal microbiota affects the permeability of the intestinal mucosa and, consequently, could be involved in the early stages of CD pathogenesis.